A Systematic Review of Literature examining the efficacy and effectiveness of the Developmental, Individual-Difference, Relationship-Based Model (DIR)/Floortime intervention for pre-adolescent children diagnosed with Autism Spectrum Disorders in majority world countries - Hinz, Anja Stefanie (Rhodes University, Faculty of Humanities, Department of Psychology, 2020)
The DIR/Floortime model focuses on the child as a holistic entity and views the treatment of Autism Spectrum Disorders in much the same way, acknowledging that every child has a unique biological profile, with their own sensory, cognitive, and affective abilities and individual strengths and weaknesses. However, researchers have primarily conducted studies in minority world countries, and thus the results of previous research are not necessarily generalisable to majority world countries (see Appendix A). The objective of this systematic review was to consult published studies conducted in majority world countries to determine whether the DIR/Floortime interventions are effective and efficacious in the treatment of preadolescent children diagnosed with Autism Spectrum Disorders. As there is limited published literature on this topic, the methodological design of a systematic review was chosen, due to its ability to locate and highlight gaps in the literature for a specific topic. The findings highlight the need for more research to be conducted in other majority world countries and low-income and low-education families before determining whether the DIR/Floortime intervention is truly effective and efficacious in all majority world countries.
Keywords: Psychology -- South Africa; Autism spectrum disorders -- Developing countries; Autism spectrum disorders -- Research -- Developing countries; Autism spectrum disorders in children; Autism in children -- Treatment; Play therapy; D.I.R.FloortimeÂ®; Systematic review